Older adults with poor self‐rated memory have less depressive symptoms and better memory performance when perceived self‐efficacy is high. (17th December 2015) - O'Shea, Deirdre M.; Dotson, Vonetta M.; Fieo, Robert A.; Tsapanou, Angeliki; Zahodne, Laura; Stern, Yaakov
Abstract : Objective: To investigate whether self‐efficacy moderates the association between self‐rated memory and depressive symptoms in a large sample of older adults. The influence of self‐efficacy and depressive symptoms on memory performance was also examined in a subsample of individuals who reported poor memory. Methods: Non‐demented participants ( n = 3766) were selected from the 2012 wave of the Health and Retirement Study. Depressive symptomatology was assessed with the 8‐item Center for Epidemiologic Studies Depression Scale. A modified version of the Midlife Developmental Inventory Questionnaire was used as the measure of self‐efficacy. Participants were asked to rate their memory presently on a five‐point scale from Excellent (1) to Poor (5). Immediate memory and delayed memory (after a 5‐min interval) were measured by the number of correct words recalled from a 10‐item word list. Results: Multiple regression analyses revealed that negative ratings of memory were significantly associated with greater levels of depressive symptoms, with this effect being greatest in those with low levels of self‐efficacy. Additionally, greater self‐efficacy was associated with optimal objective memory performances but only when depressive symptoms were low in individuals who reported poor memory function ( n = 1196). Conclusion: Self‐efficacy moderates the relationship between self‐rated memory function and depressive symptoms. Higher self‐efficacy may buffer against the impact of subjective memory difficulty on one's mood and thereby mitigating the effect of depressive symptoms on memory. Interventions should focus on increasing perceived self‐efficacy in older adults reporting poor memory function to potentially minimize memory impairment.